Pemanfaatan Teknologi Modifikasi Cuaca sebagai Upaya Penanggulangan Bencana Hidrometeorologi di Indonesia - Magdalena Sidauruk; Herlina Juni Risma Saragih; Sugeng Tri Utomo; Pujo Widodo; Kusuma (PendIPA Journal of Science Education, 2023)
Indonesia is a country prone to hydrometeorological disasters. BNPB notes that every year Indonesia's disasters are dominated by hydrometeorological disasters, namely floods, landslides, extreme weather, karhutla and drought. The hydrometeorological disaster in Indonesia resulted in quite large economic losses. The application of TMC (Weather Modification Technology) in Indonesia has had good success. This research uses a qualitative approach with a descriptive method based on the description of the results of research that has been done previously regarding Weather Modification Technology in overcoming hydrometorological disaster efforts in Indonesia. TMC's efforts in tackling forest and land fires in 2020 and 2021 in provinces that are prone to forest fires are carried out during the rainy season transition period before the start of the dry season. Implementation of TMC in a timely manner, can shorten the time of forest and land fires in a number of areas that have high vulnerability, so that the number of karhutla incidents can be optimally suppressed. Flood control efforts in Jakarta in 2013 with TMC were carried out for 33 days in 2013 with two methods, namely the jumping process mechanism method and the competition mechanism method with the aim of accelerating the rain process before it arrives in Jakarta. The results from the TMC were a 20-50% reduction in rain in Jakarta. The application of TMC for drought management on plantations in 2014 in Riau, Central Kalimantan and North Sumatra for 120 days resulted in an additional rainfall of 198 mm/year, for the Central Kalimantan region by 254 mm/year and for the North Sumatra region by 233 mm/year. Disaster management efforts using TMC are considered effective in Indonesia. This effort is a reference for the government and policy makers for the prevention of hydrometeorological disasters in Indonesia.